Penggunaan Media Digital Dalam Membangun Brand Image Di SD Islam Al-Azhar 54 Pekanbaru - Indah Permata Sari; Novita, Lesti; Nurhasanaheni; Khairani, Rodhiyatul; Wiranda; Afriza (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
This study aims to explore the role of digital media in building the brand image of SD Islam Al-Azhar 54 Pekanbaru. As an educational institution based on Islamic values, the school optimizes the use of social media platforms such as Instagram, Facebook, WhatsApp, and TikTok to enhance visibility, create a positive image, and build public trust. The strategies implemented include planned content creation, alignment with Islamic values, active engagement with the audience, and adaptation to evolving digital trends.The findings reveal that digital media significantly supports broader communication, promotes flagship programs, and strengthens community relationships. The annual increase in student enrollment serves as evidence of the effective and responsive management of digital media. This study highlights that optimal utilization of digital media not only enhances branding efforts but also serves as a critical strategy for gaining a competitive edge in the modern education sector.